A new condition for Root Clustering in PMI regions - Mohamed Hechmi BOUAZIZI (Revista Română de Informatică și Automatică)
This paper proposes a new condition for the root clustering of a real matrix A in a complex region D defined by a polynomial matrix inequality (PMI region). For a general case, a sufficient condition is given so that the eigenvalues of A lie in D . It was shown that this condition is necessary and sufficient for some particular PMI regions including linear matrix inequality (LMI) regions, quadratic matrix inequality (QMI) regions, polynomial regions and many others.